ФІЛОСОФСЬКІ ЗОМБІ: ЛОГІКО-КОГНІТИВНА ІНТЕРПРЕТАЦІЯ - СИНИЦЯ, А. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Проаналізовано аргумент від логічної можливості філософських зомбі, який використовується в філософії свідомості задля критики фізикалізму. Виявлено зв’язок цього аргументу із аргументом від мислимості Р. Декарта. Встановлено, що концепт філософських зомбі містить низку неточностей логічного і когнітивного характеру, що доводить його недостатність у процесі критики фізикалізму. Синица А. С. ФИЛОСОФСКИЕ ЗОМБИ: ЛОГИКО-КОГНИТИВНАЯ ИНТЕРПРЕТАЦИЯ Проанализировано аргумент от логической возможности философских зомби, который используется в философии сознания для критики физикализма. Выявлено связь этого аргумента с аргументом от мыслимости Р. Декарта. Установлено, что концепт философских зомби содержит ряд неточностей логического и когнитивного характера, что доказывает его недостаточность в процессе критики физикализма. Ключевые слова: философия сознания, философские зомби, мыслимость, логическая возможность, физикализм. Synytsya A. PHILOSOPHICAL ZOMBIES: LOGIC-COGNITIVE INTERPRETATION The argument from logical possibility of philosophical zombies (p-zombies), used in philosophy of mind to critics of physicalism (philosophical concept that reduces the mental to the physical), is analyzed. Philosophical zombie is a hypothetical creature similar to human being, but deprived of consciousness, ability to experience the qualia – the subjective properties of sensory experience. The argument from the logical possibility of philosophical zombies is based on the following assumption: if a certain situation is conceivable, meaning not internally contradictory, it is logically possible. The relation of this argument and the conceivability argument by R. Descartes is showed. The notions of the assertors of zombies’ argument (D. Chalmers) and the main critics of this argument (D. Dennett, J. Searle, late R. Kirk, K. Frankish) are considered. The author is not an apologist or adherent of physicalism, however notes that the concept of philosophical zombies contains a number of logical and cognitive inaccuracies proving its insufficiency to criticize physicalism. Keywords: philosophy of mind, philosophical zombies, conceivability, logical possibility, physicalism.